Analisis Penyerapan Tenaga Kerja pada Sektor Industri Pengolahan Skala Sedang dan Besar di Kalimantan Selatan - Apriliana, Apriliana; Sa’roni, Chairul (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to analyze the effect of the development of medium and small-scale manufacturing industries on the absorption of labor in South Kalimantan. The data used is secondary data from the Central Statistics Agency in 2006-2019, using time series analysis data. The results of the study show: 1) the minimum wage has a negative and significant effect on labor absorption in the medium and large-scale manufacturing sector; 2) the output value has a negative and insignificant effect on employment in the medium and large-scale manufacturing sector; and 3) the number of business units has a positive and significant effect on the absorption of labor in the medium and large-scale manufacturing sector.